2000
DOI: 10.1016/s0168-6496(00)00016-7
|View full text |Cite
|
Sign up to set email alerts
|

PCR typing of tetracycline resistance determinants (Tet A–E) in Salmonella enterica serotype Hadar and in the microbial community of activated sludges from hospital and urban wastewater treatment facilities in Belgium

Abstract: The distribution of tetracycline resistance determinants Tet A^E was studied by PCR in 40 tetracycline-resistant Salmonella enterica serotype Hadar (S. hadar) isolates collected from human patients in 1996 and 1997, as well as in the microbial community originating from activated sludges of hospital and urban wastewater treatment facilities. A fast DNA extraction and purification method from activated sludges was used to provide amplifiable DNA. The method is based on the direct lysis of bacteria improved by b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 28 publications
(41 reference statements)
2
45
0
2
Order By: Relevance
“…These bacteria accounted for about 4.5% of all Tet r strains. This value was higher than those previously reported for lactose-fermenting coliforms (27), Salmonella serovar Typhimurium (28), Salmonella serovar Hadar (16), Aeromonas, and Enterobacteriaceae isolated from catfish, catfish ponds, and rainbow trout farms (12,13,14,37). Although environmental factors have been reported to affect the number of resistance genes carried by a single cell (11), the difference is more likely to be caused by a difference in the number of PCR primers utilized.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…These bacteria accounted for about 4.5% of all Tet r strains. This value was higher than those previously reported for lactose-fermenting coliforms (27), Salmonella serovar Typhimurium (28), Salmonella serovar Hadar (16), Aeromonas, and Enterobacteriaceae isolated from catfish, catfish ponds, and rainbow trout farms (12,13,14,37). Although environmental factors have been reported to affect the number of resistance genes carried by a single cell (11), the difference is more likely to be caused by a difference in the number of PCR primers utilized.…”
Section: Discussionmentioning
confidence: 55%
“…Dissemination of the proton-dependent tetracycline efflux protein in aquaculture environments has been reported (5,12,13,14,22,34,37). Previous work has identified the relevant genes by using DNA hybridization or PCR methods (4,12,13,14,15,16,27,28,34,37), but the nucleotide sequences of these determinants remain unknown. In the present study, we isolated numerous Tet r gram-negative fish farm bacteria and determined the DNA sequences of the Tet r genes.…”
mentioning
confidence: 99%
“…In wastewater treatment plants (WWTPs) tetracyclines have been detected both in the influent and effluent (Karthikeyan & Meyer 2006). Bacteria resistant to tetracycline and genes encoding tetracycline resistance (tet-genes) are also commonly described in WWTPs (Guillaume et al 2000;Auerbach et al 2007;Zwenger & Gillock 2009). One study has shown that the fraction of tetracycline-resistant bacteria increased with increasing concentrations of influent tetracycline (Kim et al 2007a,b).…”
Section: Introductionmentioning
confidence: 99%
“…The application of PCR to detecting AR genes in both bacterial isolates and environmental samples has provided additional insights into the occurrence of AR in various environments (4,5,9,15,24). The demonstration that AR genes are detectable in groundwater samples collected downstream of livestock production environments and animal waste lagoons (4,9) has further heightened concerns about the role of agriculture in the dissemination of AR (13,32).…”
mentioning
confidence: 99%